Creativity and effectiveness in organizations. A new approach to an old question = Twórczość i efektywność w organizacjach. Nowe podejście do starego pytania - Bratnicka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
Juxtaposing the important insights of previous multilevel research, the following overarching question emerges as the central concern of this article: How do emergent processes and top- management initiatives affect the impact of organizational creativity on organizational effectiveness? To shed light on this question, I direct attention to bottom- up emergent processes and top down management initiatives, which, I argue, offers important opportunities for the genesis of additional creativity effects.
Keywords: twórczość organizacyjna; efektywność organizacyjna; procesy emergencji; kształtowanie zasobów; kadra zarządzająca; organizational creativity; multilevel approach; emergent processes; creative resourcing; manager